2010
DOI: 10.1104/pp.110.154062
|View full text |Cite
|
Sign up to set email alerts
|

CELLULOSE SYNTHASE9 Serves a Nonredundant Role in Secondary Cell Wall Synthesis in Arabidopsis Epidermal Testa Cells      

Abstract: Herein, we sought to explore the contribution of cellulose biosynthesis to the shape and morphogenesis of hexagonal seed coat cells in Arabidopsis (Arabidopsis thaliana). Consistent with seed preferential expression of CELLULOSE SYNTHASE9 (CESA9), null mutations in CESA9 caused no change in cellulose content in leaves or stems, but caused a 25% reduction in seeds. Compositional studies of cesa9 seeds uncovered substantial proportional increases in cell wall neutral sugars and in several monomers of cell wall-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 48 publications
5
75
0
Order By: Relevance
“…Overexpression of a mutant allele of the Arabidopsis CESA7 gene, named fra5, resulted in changes in cellulose synthesis during primary wall formation (reduced thickness of the cell wall and cell elongation) as well as causing a dominant-negative effect on cellulose synthesis during secondary wall formation (Zhong et al, 2003), as was also suggested in the case of the widely recognized secondary wall-specific AtCESA7 (MUR10), being required for normal primary cell wall carbohydrate composition in mature leaves, normal plant growth, hypocotyl strength, and fertility (Bosca et al, 2006). Another study shows that despite CESA9 having already been classified as a primary cell wall CESA (Desprez et al, 2007;Persson et al, 2007), a nonredundant role was shown in secondary cell wall thickening in the seed coat (Stork et al, 2010). The rice (Oryza sativa) brittle culm11 mutant has shown both altered primary (increased callose, pectic arabinan, and xylan) and secondary (brittleness of the culm, abnormal secondary structure, decreased wall thickness, and reduced cellulose content) wall composition (Zhang et al, 2009), further supporting the possibility of cross-talk and overlapping functions between the primary and secondary CESAs.…”
Section: Primary and Secondary Cesas Can Be Part Of The Same Protein mentioning
confidence: 81%
“…Overexpression of a mutant allele of the Arabidopsis CESA7 gene, named fra5, resulted in changes in cellulose synthesis during primary wall formation (reduced thickness of the cell wall and cell elongation) as well as causing a dominant-negative effect on cellulose synthesis during secondary wall formation (Zhong et al, 2003), as was also suggested in the case of the widely recognized secondary wall-specific AtCESA7 (MUR10), being required for normal primary cell wall carbohydrate composition in mature leaves, normal plant growth, hypocotyl strength, and fertility (Bosca et al, 2006). Another study shows that despite CESA9 having already been classified as a primary cell wall CESA (Desprez et al, 2007;Persson et al, 2007), a nonredundant role was shown in secondary cell wall thickening in the seed coat (Stork et al, 2010). The rice (Oryza sativa) brittle culm11 mutant has shown both altered primary (increased callose, pectic arabinan, and xylan) and secondary (brittleness of the culm, abnormal secondary structure, decreased wall thickness, and reduced cellulose content) wall composition (Zhang et al, 2009), further supporting the possibility of cross-talk and overlapping functions between the primary and secondary CESAs.…”
Section: Primary and Secondary Cesas Can Be Part Of The Same Protein mentioning
confidence: 81%
“…S2). As viewed by scanning electron microscopy (SEM), Arabidopsis seed coat epidermal cells appear as hexagonal epidermal cells outlined by reinforced radial cell walls with a volcanoshaped columella (Beeckman et al, 2000;Western et al, 2000;Stork et al, 2010). Inspection of mature dry seeds of the three mutant lines revealed no alteration in radial cell walls, columella, or mucilage pockets around the columella (Fig.…”
Section: The Structure Of the Mucilage Planar Surface Is Altered In Cmentioning
confidence: 99%
“…15,[17][18][19] The molecular details of the primary to secondary cell wall transition and mechanisms that underlie the cross talk between primary and secondary cell wall biosynthesis are largely unknown.…”
Section: Functional Analysis Of Complexes With Mixed Primary and Secomentioning
confidence: 99%
“…13 Another example came from the most recent finding that primary CESAs have function in the formation of secondary cell walls during seed coat development. 14,15 Specifically, CESA5 is responsible for mucilage attachment and CESA2, 5 and 9 contribute to secondary cell wall biosynthesis in the columella cells. 16 These findings suggest that the distinction between primary and secondary CESAs might not be as strict as initially defined.…”
Section: Functional Analysis Of Complexes With Mixed Primary and Secomentioning
confidence: 99%